Book Reviews Vol12 no3 - Miguel Debono; Jackie Schiller; Robert Shaw (Scottish Journal of Residential Child Care)
The books reviewed in this article are: Barton, S., Gonzalez, R., & Tomlinson, P. (2012). Therapeutic residential child care for children and young people: An attachment and trauma-informed model for practice. London: Jessica Kingsley, 287 pp., ISBN 978 1 84905 255 9 (pb), £22.99.